Analisis Kesehatan Bank pada Perbankan Yang Terdaftar di BEI - Arsyanti, Ananda Ira; Askandar, Noor Shodiq; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
In this study aims to determine the level of banking health during the pandemic. Knowing the level of soundness of the company can help debtors make the right decisions, can help the company know the weaknesses and strengths that exist in the company. This research uses quantitative descriptive research with banking research objects registered on the IDX in 2021. The results show that all banks listed on the IDX are very healthy in terms of CAR ratios, seen from NPLs, it shows that several banks are in very healthy, healthy, moderately healthy, unhealthy and unhealthy positions and there are non-credit Islamic banks. From the NPM and ROA ratios, several banks experienced losses. BOPO shows that several banks are very healthy, Bank Ganesha is healthy, Bank Oke Indonesia is quite healthy, some are not healthy and some are not. The LDR ratio shows that some are very healthy, commercial banks are healthy, some banks are quite healthy, some are not healthy and there are other banks that are not healthy.Keywords : Bank, financial reports, analysis of financial statements, the soundness of the bank, the CAMEL method